ODSTP: a single-objective model for optimizing school transport in sub-Saharan African metropolises - Kpinna Tiekoura , Coulibaly; Koffi, Kanga; Moustapha, Diaby (International Journal of Engineering and Technology, 2024)
The density of road traffic in large cities in sub-Saharan Africa causes enormous inconvenience to pupils and students, including numerous late arrivals at school and a general state of stress leading to poor school results. In this work, we propose a single-objective optimization model based on a transport-on-demand approach, taking quality of service into account. Our model has the advantage of minimizing both the total tour distance, the tour duration and the route cost (the sum of the fixed vehicle cost and the running cost). To solve our problem, we use a meta-heuristic: the tabu search method.